PENGARUH MEDIA SOSIAL YOUTUBE TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI STAMBUK 2018 UNIMED (Manajemen & Bisnis Jurnal, 2023)
Abstract. This studi aims to determine the effect of Youtube Learning Media on student achievment in economics Education at the State University f Medan. The type of research is quantitative research using IBM SPSS version 22. Data collection techniques are through questionnaries, observation and documentation. The result of the study show that there is a positive and significant effect of Youtube Learning Media on learning achievment where t acount was 7.638 which was greater than the t table of 1,990.